(untitled) (Sri Lanka Journal of Indigenous Medicine (SLJIM), 2022)
Urolithiasis can be defined as the process of forming stones in the kidney, bladder and urinary tract. It is found that 1 in 20 people develop kidney stones at some stage in their life time. Treatment includes relief of pain, hydration and antibiotics. Although many advanced allopathic medicines are available in the modern world, most people have been using the herbal medical treatments owing to its less side effects and low cost. Salacia reticulata is one of the herbs used to cure the urinary stones in the human body. This research was conducted to evaluate In-vitro anti-urolithiatic activity of Salacia reticulata stem extract on experimentally prepared calcium oxalate stones. Methanolic plant extract was prepared by using the soxhlet apparatus. Artificial stones of calcium oxalate were prepared by homogenous precipitation method. Semi-permeable membrane bags were prepared from chicken eggs. One sample of negative control, four samples of positive control with 10, 20, 30, 40 mg of standard drug cystone and four other samples with 10, 20, 30, 40 mg of methanolic extract of Salacia reticulata were prepared separately. The prepared samples were incubated for 7 hours at 37 oC in pH 7.4. Titrimetric method was followed in order to determine the anti-urolithiatic activity. The mean (±SD) dissolution percentage of extract of Salacia reticulata on experimentally prepared calcium oxalate for 10, 20, 30 and 40mg were 34.8, 38.6, 40.4 and 45.0% respectively. The dissolution percentage significantly increased with concentration. Dissolution percentages of cystone on artificial calcium oxalate stones for 10, 20, 30, 40 mg were 64.8, 70.6, 75.8 and 79.6% respectively. Both the methanolic extract of S. reticulata and the standard drug has a positive correlation with its concentration. The results of this study have confirmed the long history of the use of Salacia reticulata in traditional medicine for the treatment of Urolithiasis. Keywords: Salacia reticulata, Anti-urolithiatic, Cystone, Methanolic extract.